2008
DOI: 10.1007/978-3-540-69389-5_38
|View full text |Cite
|
Sign up to set email alerts
|

Towards Large Scale Semantic Annotation Built on MapReduce Architecture

Abstract: Abstract. Automated annotation of the web documents is a key challenge of the Semantic Web effort. Web documents are structured but their structure is understandable only for a human that is the major problem of the Semantic Web. Semantic Web can be exploited only if metadata understood by a computer reach critical mass. Semantic metadata can be created manually, using automated annotation or tagging tools. Automated semantic annotation tools with the best results are built on different machine learning algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Now it is popular in text mining of various applications [18], especially Natural Language Processing (NLP) and Machine Learning (ML), as the MapReduce paradigm has emerged as a highly successful programing model for large-scale data-intensive computing applications [19]. Laclavik et al presented a pattern of annotation tool based on MapReduce architecture to process large amount of text data [20]. Lin and Dyer discussed the processing method of data intensive text based on MapReduce, such as parallelization of EM algorithm and HMM model [4].…”
Section: Related Workmentioning
confidence: 99%
“…Now it is popular in text mining of various applications [18], especially Natural Language Processing (NLP) and Machine Learning (ML), as the MapReduce paradigm has emerged as a highly successful programing model for large-scale data-intensive computing applications [19]. Laclavik et al presented a pattern of annotation tool based on MapReduce architecture to process large amount of text data [20]. Lin and Dyer discussed the processing method of data intensive text based on MapReduce, such as parallelization of EM algorithm and HMM model [4].…”
Section: Related Workmentioning
confidence: 99%
“…They commented that UIMA and GATE would benefit from adopting MapReduce. Laclavik et al [16] demonstrated using Ontea [17] with Hadoop. This study presents GATECloud.net-the adaptation of the GATE infrastructure to the cloud, following the PaaS paradigm. It enables researchers to run their NLP applications without the significant overheads of re-implementing their algorithms for MapReduce and understanding Amazon's IaaS APIs.…”
Section: Large-scale Text Mining and Compute Cloudsmentioning
confidence: 99%
“…Interested fellows leave traces in the digital space, sometimes even without being aware of it. For example: evaluations, recommendations, annotations, inscriptions on a virtual wall [45,46]. Interested fellows communicate with others, forming communities of those sharing interests.…”
Section: Cognitive Traveling In Digital Spacementioning
confidence: 99%